The study of neologisms in contemporary English - Pernebayeva, Diana Daniyarovna; Sultonova, Nigora Abduganievna (The Lingua Spectrum, 2026)
This article discusses how the English language is changing rapidly, specifically between 2020 and 2026, with a primary focus on the emergence of neologisms. As digital communication and socio-political shifts undergo a global transformation, the processes of word formation are also evolving, and traditional rules for creating new words have become increasingly flexible. Additionally, the study examines the most productive morphological processes through which new words are created, such as blending, compounding, and semantic shift. The research explores why and how these terms appear and what factors motivate people to integrate them into their daily lives. The analysis is predicated on qualitative data derived from digital media, contemporary dictionaries, and professional communication. In this context, the study emphasizes that neologisms are not merely temporary linguistic trends but are essential components of modern communication that reflect our changing world. By examining these lexical shifts, we can better understand the current direction of the English language and its future development.